Possibilidades e desafios da inserção do tema Floresta Amazônica no contexto educacional - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
The environmental and social scenario that is being designed, puts in place, the prevailing paradigms of which sustain the uncertainty of continuity of human life on the planet. In this scenario, the Amazon stands out, given its importance, regional, national and planetary for environmental dynamics of the biosphere. However, the inability to deal with the forest is relevant. When looking for ways out, education points out as a safe alternative for this to happen, given its emphasis on taking the human being to successive searches for improvements, supported by science, research, technology, philosophy, arts, literature, reflection, action . However, acting in such uncertain times, requires competent and skilled professionals to understand the constant socio-economic-political-environmental changes that surround us. Prioritizing interdisciplinary training with a broad view of relationships is urgent as a necessity, as this way we can reduce gaps that put everyone at risk. Thus, this study prevailed on these assumptions and made use of the analysis of the course “The Amazon Forest and its multiple dimensions”, this being a sample of courses available for teacher training. The objectives of this work are focused on analyzing the conception of the teachers, who participated in the immersion course, on the inclusion of the “Amazon rainforest” theme in the classroom discussion. How to understand the course matrix and its contribution to the development of contents of the National Common Curricular Base - BNCC. Also accompanied by an understanding of the appropriation of the most recent scientific concepts about the forest developed in the process of in situ formation. In addition to observing the discussion of concepts from classroom training. The research is of a qualitative nature, being characterized as a case study and using research modalities that deal with participant observation, direct observation, structured and semi-structured interviews, diaries and concept maps. Their analyzes include the description of the data, as well as the latency of content on certain responses. 23 teachers participated in this study in the first moment and 8 in the second moment, from SEMED and SEDUC from Amazonas. The results achieved allow us to reflect on the teachers' conception regarding the insertion of the Amazon rainforest theme in the BNCC, pointing out the need to insert these data as a source of knowledge about sustainability and a source of knowledge about the local reality. From the immersion, it was found that learning and ways of understanding knowledge from the basis of interdisciplinarity, triggering possible changes in the cognitive structure of the teachers who participated in the course. When staying in the classroom, it was observed that the changes and the apprehension of knowledge that were initiated in the course are present in the classroom, but when sharing them with the students, the teachers, in their majority choose traditional didactic models. , with tests for new methodologies. Hence, it can be understood that training focused on specific themes with openness to dialogue provides the expansion of knowledge, causing changes. However, in the classroom, effectiveness depends on other variables, such as new ways of conducting classes, which need to be investigated.
Keywords: Desenvolvimento cognitivo; Ensino e aprendizagem; Professores - Formação; Educação ambiental; Floresta Amazônica; CIÊNCIAS AGRARIAS; Amazônia; Educação; Sustentabilidade; Formação de Professores